Training on Contextual Teaching Modules Based on Merdeka Curriculum for Early Childhood Education Teachers in Border Areas - A. Ahmad Ridha; Azwar Anwar; Bimo Aji Nugroho (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Teaching modules are an important component that supports teachers in planning, implementing, and evaluating relevant and contextualized learning. The Merdeka Curriculum teaching module training is focused on empowering teachers to be able to develop teaching modules that are flexible, innovative, and in accordance with the characteristics of students. The training aims to increase the understanding of PAUD teachers in developing contextual teaching modules based on the independent curriculum. Through training, teachers are equipped with practical skills and knowledge to develop lesson plans, choose appropriate learning strategies, and conduct competency-based assessments. The target partners are teachers at Nurul Iman Malinau Kindergarten in North Kalimantan In this activity there are 5 processes or stages, first socialization, training, technology application, program evaluation and follow-up plans. The essence of this service is how PAUD teachers are able to develop contextual teaching modules based on the independent curriculum. The first step that must be taken by teachers is the ability to formulate learning objectives from the flow of learning objectives that are relevant and in accordance with the characteristics of students. This activity does not only take place in one meeting, but is also carried out online to strengthen the results of the teaching module prepared by the teacher. From the results of the implementation of the teaching module preparation, it was found that the results of the teaching module work prepared were better than before. Teachers are able to develop a more complex and more elaborated material accompanied by assessments to measure the ability of students.